Financial development and unemployment in Malaysia / Hii Puong Hung - Hii , Puong Hung (2020)
In the past decades, the topic financial development and economic growth has been popularly discussed by scholars. From the past literature, financial development is an important component in promoting economic growth. However, there has been less study about the relationship of financial development and unemployment rate. Therefore, this study aims to investigate the relationship between the financial development and unemployment rate in the case of Malaysia from year 1981 until 2018. This study analyses the relationship by using two model equations to test separately the effect of each financial development indicators (Domestic Credit to Private Sector and Stock Market Capitalization) on the unemployment rate. Autoregressive Distributed Lag (ARDL) method and Cumulative Sum (CUSUM) control chart have been used to test the long run and short run relationships of financial development variable and unemployment rate in Malaysia. As the results, this study finds that there is a significant long-term relationship of financial development and unemployment rate for both models. However, results also revealed that the short run relationship among the financial development and unemployment rate is not significant. This shows that the financial development indicators need to take time (long term) in exerting its effect on the economic variables (unemployment rate) in the case of Malaysia. Therefore, policymakers are suggested to plan their regulations in a long-term way by taking into the consideration of implementing lag.